Short- and long-run labor market adjustment to import competition - Juan S. Blyde; Matias Busso; Kyunglin Park; Dario Romero Fonseca (Inter-American Development Bank (IDB), 2023)
By exploiting spatial variation in import exposure arising from initial differences in industry specialization, we analyze how local labor markets in Mexico adjusted to increased Chinese-import competition over different time horizons. The initial adjustment to the shock took various forms: a decline in the number of wage employees, a substitution of wage employees with piece-rate or outsourced workers, and a substitution of formal employees with informal employees. The negative effects on employment were mainly associated with job destruction from exiting firms, particularly those that were small and medium-sized. During periods in which employment fell, the population that actively participated in the labor force fell. The negative short- and medium-run effects mostly disappeared after 20 years.
Keywords: F14; F16; J23; 330; Import competition; Local labor markets; Employment; Mexico